Sublethal effects of the insecticidal fusion protein ω‐ACTX‐Hv1a/GNA on the parasitoid Eulophus pennicornis via its host Lacanobia oleracea. Issue 3 (23rd May 2015) - Nakasu, Erich YT; Karamaouna, Filitsa; Partsinevelos, Georgios K; Abd El Halim, Hesham M; Fitches, Elaine C; Pyati, Prashant; Gatehouse, John A; Gatehouse, Angharad MR; Edwards, Martin G
Abstract: BACKGROUND: The neurotoxin peptide ω ‐ACTX‐Hv1a, fused to the carrier molecule GNA, presents potential for insect control as a biopesticide, being orally toxic to insect pests from different orders. However, thorough evaluation is required to assure its safety towards non‐target invertebrates. Effects of this novel biopesticide on the parasitoid Eulophus pennicornis via its host Lacanobia oleracea are presented. RESULTS: Hv1a/GNA did not cause mortality when injected or fed to fifth‐stage L. oleracea, but caused up to 39% reduction in mean larval weight ( P < 0.05) and increased developmental time when injected. When fed, GNA, but not Hv1a/GNA, caused ∼35% reduction in larval weight, indicating that host quality was not affected by the fusion protein. Although GNA and Hv1a/GNA were internalised by the hosts following ingestion, and thus were available to higher trophic levels, no significant changes in the rate of E. pennicornis parasitism occurred. Number of parasitoid pupae per host, adult emergence and sex ratio were unaffected by GNA‐ or Hv1a/GNA‐treated hosts ( P > 0.05). The fusion protein was degraded by parasitoid larvae, rendering it non‐toxic. CONCLUSION: Hv1a/GNA has negligible effects on the parasitoid, even under worst‐case scenarios. This low toxicity to these insects is of interest in terms of biopesticide specificity and safety to non‐target organisms. © 2015 Society of Chemical Industry